A behavioral approach to asset pricing - Shefrin, Hersh (Amsterdam ; Boston : Elsevier Academic Press, 2005)
This book provides a much needed bridge between behavioural finance and traditional asset pricing theory,so that the insights that the two fields offer can complement each other.
Includes bibliographical references (p. [457]-471) and index.
aia 29/04/13
Loans
Keywords: Capital assets pricing model; Risk management; Asset pricing